Interest Rate and Loan Default in Financial Institutions - Twesiime, Monica; Tushabe, Charlotte; Ninsiima, Apophia; Tayebwa, John; Eze, Val Hyginus Udoka (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
The study was carried out to examine the relationship between interest rate and loan default in Pride Microfinance in Ishaka-bushenyi municipality, Bushenyi District, a case of Pride Microfinance Ishaka branch. This study was guided by a mixed research design. Questionnaires and interviews were used as data collection instruments. A purposive sampling technique was used to sample 50 respondents. It was found out that there are high costs of getting business loans by borrowers because of a lack of collateral. The high interest rate level on the borrowers leads to loan default among business borrowers because the profit margin is very low. It was also found out that the possible solutions to reduce loan default were proper loan assessment, motivating good loan clients, reducing interest rates and proper loan monitoring. Also, financial institutions should tighten and follow the possible solutions to minimize high interest rates to favour business borrowers for greater productivity. It was recommended that though the availability and accessibility of loanable funds is very important, the Institution could consider lowering interest rates to enhance loan on time loan repayment. The Institutions could consider the establishment of micro insurance to protect customers. There should be increased monitoring of loan to ensure that funds are not diverted, loans are used for the intended purpose and repayment made on time. The study concluded that financial Institutions have to reduce the costs of getting business loans and interest rate which would encourage borrowers to obtain business loans to effectively operate their business activities and as well as repaying the loans